(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Mashaparni is one of the important medicinal plant mentioned in Ayurveda literature. It is mentioned under important groups in Ayurveda like “Jivaniya mahakashaya, Shukrajanana gana etc. In spite of being mentioned in premium groups this herb is not so popular and mostly found adulterated in trade. It usually comes as a weed in tropical and subtropical regions of India. In this study we have highlight therapeutic benefits of this easily available but overlooked and adulterated medicinal plant Mashaparni. The author has identified the niche pockets of Mashaparni and collected its seeds for multiplication and propagation through cultivation for sustainable supply of its raw material.